Peningkatan Literasi Lingkungan di Kelurahan Banyurip Kota Pekalongan Melalui Sosialisasi Pemanfaatan Sampah Dapur Berbasis Partisipasi Kader PKK - Nurhidayah, Ika Amiliya; Saffanah, Rifkah; Rani, Fifi Aulia; Mahmudah, Nailil; Muayanah, Bawon Tri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Kelurahan Banyurip is one of the administrative areas in South Pekalongan Sub-district, Pekalongan City, which is geographically located in a densely populated area and is one of the urban villages with a high level of domestic activity. In recent years, this area has experienced rapid residential growth. Dense household activities in this area directly contribute to the high production of household waste, especially waste from the kitchen. In response to this, researchers tried to conduct a socialization targeting PKK cadres with the aim of increasing the environmental literacy of Banyurip Village PKK cadres through socialization of kitchen waste utilization. This socialization activity uses the educatif empowerment method which emphasizes the delivery of information and knowledge in a structured manner in the form of lectures and discussions to the community. The results of the socialization activity on the utilization of kitchen waste in Banyurip Village show the enthusiasm and interest of the community in alternatives to the use of kitchen waste wisely and more environmentally friendly. The positive response from the community was marked by an increased awareness of the importance of utilizing kitchen waste wisely and in an environmentally friendly manner. The introduction of methods for processing organic waste into compost, eco-enzyme, and maggot cultivation not only provides new insights, but also opens up opportunities for the economic and ecological utilization of kitchen waste that was previously considered useless.